Proceedings of the Symposium on Eye Tracking Research and Applications 2014
DOI: 10.1145/2578153.2578208
|View full text |Cite
|
Sign up to set email alerts
|

Predicting an observer's task using multi-fixation pattern analysis

Abstract: Since Yarbus's seminal work in 1965, vision scientists have argued that people's eye movement patterns differ depending upon their task. This suggests that we may be able to infer a person's task (or mental state) from their eye movements alone. Recently, this was attempted by Greene et al. [2012] in a Yarbus-like replication study; however, they were unable to successfully predict the task given to their observer. We reanalyze their data, and show that by using more powerful algorithms it is possible to pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 13 publications
1
40
0
Order By: Relevance
“…Consistent with other studies (Borji & Itti, ;Kanan et al, 2014), we found that a subject's task can be inferred solely from their eye movements. Our algorithms were most successful when judging observer's tasks from their own history of eye movement patterns, from which we conclude that, at least for these tasks, observers have idiosyncratic scanpath routines.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with other studies (Borji & Itti, ;Kanan et al, 2014), we found that a subject's task can be inferred solely from their eye movements. Our algorithms were most successful when judging observer's tasks from their own history of eye movement patterns, from which we conclude that, at least for these tasks, observers have idiosyncratic scanpath routines.…”
Section: Resultssupporting
confidence: 92%
“…This approach is similar to the method used by Greene, Liu, and Wolfe (2012) and later by Kanan et al (2014). The summary statistics algorithm only captures the simplest temporal statistics, and it ignores all spatial properties and more complex temporal characteristics.…”
Section: Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…States of the model are typically represented by ROIs and state transitions are calculated as the transition probability between the different ROIs (Kanan et al, 2014).…”
Section: Probabilistic Scanpath Comparisonmentioning
confidence: 99%